High-throughput development of genome-wide locus-specific informative SSR markers in wheat - Li, Lei; Sun, Fayu; Wu, Di; Zhen, Fei; Bai, Guihua; Gao, Derong; Li, Tao (Science China. Life sciences, 2017)
Dear Editor,Although simple sequence repeat（SSR）markers are not new,they are still useful and often used markers in molecular mapping and marker-assisted breeding,particularly in developing countries.However,locus-specific SSR markers could be more useful and informative in wheat breeding and genetic studies.In the present study,221,911 locus-specific SSR markers were designed.Verification of polymorphisms showed that the proportion of polymorphic markers increases with an increase in SSR size.